Analisis Yuridis Penerapan Perlindungan Hukum dalam Melindungi Pengguna Layanan Internet Banking dari Cyber Crime - Tri Nugraheni; Aksi Sinurat; Darius Antonius Kian (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the juridical application of legal protection in protecting internet banking service users from cyber crime. This research is a type of empirical juridical research, or called field research, which examines the applicable legal provisions and what happens in the reality of society. Empirical juridical research is legal research on the enactment or implementation of normative legal provisions in action on every legal event that occurs in society. The results of this study show: (1) The implementation of legal protection provided by the East Nusa Tenggara Regional Development Bank has not been fully implemented properly because victims have not felt protected by the regulations implemented by the East Nusa Tenggara Regional Development Bank. (2) The responsibility of legal protection provided by the Regional Development Bank of East Nusa Tenggara is to follow up and examine complaints of problems of victims of cyber crime and will examine all transactions that occur and carry out legal protection responsibilities by providing assistance and reporting problems that occur to be followed up according to applicable laws and regulations. In accordance with the results of this study, it is hoped that there will be an increase in legal protection and a quick response to users of internet banking services and a form of legal protection that is specifically regulated to protect customers from increasingly widespread cyber crime.